Development of advanced phospholipid vesicles loaded with Lippia citriodora pressurized liquid extract for the treatment of gastrointestinal disorders. (1st February 2021) - Leyva-Jiménez, Francisco-Javier; Manca, Maria Letizia; Manconi, Maria; Caddeo, Carla; Vázquez, José Antonio; Carbone, Claudia; Lozano-Sánchez, Jesús; Arráez-Román, David; Segura-Carretero, Antonio
Highlights: PLE extract from L. citriodora was successfully incorporated in nanovesicles. Five different phospholipid formulations were developed and tested in Caco-2 cells. Phospholipid vesicles were incorporated into a food matrix showing good stability. PG-PEVs and glucidex-PG-PEVs showed the best results in stability tests. Chondroitin-PG PEVs improved the Caco-2 viability in an antioxidant assay. Abstract: Pressurized liquid extraction was performed to obtain a phytocomplex from Lippia citriodora leaves rich in bioactive compounds. The extract was loaded in phospholipid vesicles to improve its protective effect against oxidative stress in the intestine. The phytochemicals were identified and quantified by HPLC-ESI-TOF-MS. The extract was incorporated in liposomes and penetration enhancer-containing vesicles (PEVs) modified with glucidex, a dextrin, and a biopolymer obtained from Chimaera monstrosa. The PEVs were smaller than liposomes ( 150 vs 370 nm) and more stable, according to accelerated aging tests. The integrity of the vesicles in acidic or neutral pH and high ionic strength or in milk whey was assessed. The cytocompatibility of the formulations and their ability to protect Caco-2 cells against oxidative stress were confirmed in vitro and compared with two commercial extracts of L. citriodora . The results confirmed the suitability of formulations to be used in functional foods to protect the intestine from oxidative stress.